PENGARUH PROFITABILITAS, LEVERAGE, UKURAN PERUSAHAAN, OUTSIDER OWNERSHIP, DAN REPUTASI KAP TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Trade, Services and Investment Yang Terdaftar Di Bursa Efek Indonesia 2014-2016) - Raja Multi Konvokesen Adiman; Enni Savitri; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to examine: 1) the effect of profitability on timeliness of financial reporting, 2) the influence of leverage on timeliness of financial reporting, 3) the effect of firm size on timeliness of financial reporting, 4) the influence of outsider ownership on timeliness of financial reporting, 5) the effect of auditor’s firm reputation towards timeliness of financial reporting. The population used in this study is all trade, services, and investment company listed in Indonesia Stock Exchange in 2014-2016. Samples were determined by using purposive sampling method and obtained sample of 78 companies. The type of data used in this study is secondary data. Data analysis was done by multiple regression analysis using SPSS program. The results of the research indicate that: 1) profitability influences on timeliness of financial reporting, 2) leverage has no effect ontimeliness of financial reporting, 3) firm size influences ontimeliness of financial reporting, 4) outsider ownership influences on timeliness of financial reporting, 5) auditor’s firm reputation influences on timeliness of financial reporting.Keywords : Profitability, Leverage, Firm Size, Outsider Ownership, Auditor’s Firm Reputation, Timeliness of Financial Reporting.